The Legacy of Justice Brennan: Constitutionalization of the Left-Liberal Political Agenda - Lino A. Graglia (Washington University Law Quarterly, 1999)
Justice William J. Brennan, Jr. served on the United States Supreme Court for more than a third of a century, from 1956 to 1990, long after President Eisenhower, who foolishly appointed him to gain a temporary political advantage, was gone from office and had passed away. Justice Brennan, previously an obscure state court judge in New Jersey, made a lot of his lucky appointment, so much so that he made himself arguably the most important figure in American public life in the second half of the twentieth century, even though most of his fellow citizens would not have recognized his name. His importance derived, however, from his exercise of a power he had not been granted.
Keywords: Liberalism; William J. Brennan; 1906-1997; Constitutional interpretation; Judicial activism; United States. Supreme Court